2001
DOI: 10.1093/jhered/92.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Triplet-Repeat Microsatellites Shared Among Hard and Soft Pines

Abstract: Vascular plant species have shown a low level of microsatellite conservation compared to many animal species. Finding trans-specific microsatellites for plants may be improved by using a priori knowledge of genome organization. Fifteen triplet-repeat microsatellites from hard pine (Pinus taeda L.) were tested for trans-specific amplification across seven hard pines (P. palustris Mill., P. echinata Mill., P. radiata D. Don., P. patula Schiede et Deppe, P. halepensis Mill., P. kesiya Royle), a soft pine (P. stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 24 publications
4
37
1
Order By: Relevance
“…According to Kutil and Williams (2001) compound microsatellites are less persistent than perfect microsatellites because the former contain more imperfections and deletions and probably represent the last stage before degradation. Perfect microsatellites were the most frequent type in our study, followed compound and the imperfect microsatellites, and this suggests a certain degree of sequence stability and conservation in their recent evolution, although it is also possible that the use of enriched libraries may have enhanced the number of perfect microsatellites (Moriguchi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kutil and Williams (2001) compound microsatellites are less persistent than perfect microsatellites because the former contain more imperfections and deletions and probably represent the last stage before degradation. Perfect microsatellites were the most frequent type in our study, followed compound and the imperfect microsatellites, and this suggests a certain degree of sequence stability and conservation in their recent evolution, although it is also possible that the use of enriched libraries may have enhanced the number of perfect microsatellites (Moriguchi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Plant microsatellites have been developed for germplasm conservation, cultivar identification and for assessing genetic diversity not only in crops such as tomato (He et al, 2003a) and peanut (He et al, 2003b;Ferguson et al, 2004) but also in marijuana (Alghanim and Almirall, 2003) and perennial plants such as the Melaleuca (the tea tree) (Rossetto et al, 1999), Pinus (Kutil and Williams, 2001), Cryptomeria (Moriguchi et al, 2003) and Litchi Genetics and Molecular Biology, 29, 1, 90-96 (2006) Copyright by the Brazilian Society of Genetics. Printed in Brazil www.sbg.org.br (Viruel and Hormaza, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Further work is required to test whether three loci would suffice to identify all individuals from a larger population of host trees. However, if the three primer pairs used in this study were found to be insufficient at discriminating between larger populations of pine trees, a number of alternative microsatellite primers are available (Kutil & Williams, 2001; (Smith et al, 1965;Moser, 1997). We have a sequence from a basidiome of S. flavidus (AY641461) collected in NE Scotland which is 99.2% similar over 645/653 bp with L54115, indicating that S. umbonatus should indeed be regarded as a synonym of S. flavidus.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, transfer to other subgenera or nonPinus coniferae has been reported to be poor (Echt et al 1996;Fisher et al 1998), although optimisation of polymerase chain reaction (PCR) conditions increased transfer rates for some of these loci (Karhu et al 2000). Kutil and Williams (2001) reported that tri-nucleotide microsatellites from low-copy genomic regions increased transfer rates within Pinaceae. Unlike previous investigators, they noted that both flanking regions and repeat motifs were highly conserved in soft and hard pines.…”
Section: Introductionmentioning
confidence: 99%